Raman Spectroscopy - Morari do Nascimento, Gustavo (IntechOpen, 2018)
This book gives a wide overview of the state-of-the-art applications of Raman spectroscopy in characterization of materials and biomaterials. The Raman signal is intrinsically smaller than other vibrational techniques; however, mainly through intensification processes, such as resonance Raman (RR) and surface-enhanced Raman spectroscopy (SERS), the Raman cross section can be strongly amplified. Thoroughly in these signal amplifications, the study of a diversity of chemical systems and the use of Raman technique for in situ and in vivo measurements is possible. The main goal of this book is to open up to an extended audience the possibilities of uses of Raman spectroscopy. In fact, this collective work will be beneficial to students, teachers, and researchers of many areas who are interested to expand their knowledge about Raman spectroscopy applied to nanotechnology, biotechnology, environmental science, inorganic chemistry, and health sciences.